QUALITATIVE ANALYSIS OF SALAK LEAF EXTRACT (SALACCA SUMATRANA) - Jalilah Jalilah Azizah Lubis; Sahlan Tuah Harahap; Fatma Suryani Harahap (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Qualitative analysis research of salak leaf extract has been carried out, where the salak leaf extract Padangsidimpuan has characteristic with a larger size and does leaf has a meat which has a distinctive sour taste, because of its acid content, it is processed in the form of salak leaf (Salacca sumatrana) which aims to analyze the levels of secondary metabolites in salak leaf which are expected to be a cholesterol-lowering herbal medicine. With the appropriate qualitative analysis of salak leaf using the extraction method, namely the maceration method with methanol solvent, the results obtained that salak leaf contains Secondary metabolites consisting of alkaloids, phenolics, saponins, tannins, terpenoids, however, it does not contain flavonoids and steroids.